Предмет: Алгебра,
автор: Анжелика002
(x^2-x)^2-12(x^2-x)=0
Ответы
Автор ответа:
0
(x^2-x) заменешь на t
будет t^2-12t=0
t(t-12)=0
t=0 or t=12
Теперь обратную замену
x^2-x=0 x^2-x=12 тут решается обычно по дискрименанту
x(x-1)=0 думаю справишься
x=0 or x=1
будет t^2-12t=0
t(t-12)=0
t=0 or t=12
Теперь обратную замену
x^2-x=0 x^2-x=12 тут решается обычно по дискрименанту
x(x-1)=0 думаю справишься
x=0 or x=1
Похожие вопросы
Предмет: Математика,
автор: nuralibeysenbaev
Предмет: История,
автор: sabocokajgerim
Предмет: Математика,
автор: sendipedraza
Предмет: Геометрия,
автор: GrizyGranit
Предмет: Информатика,
автор: Frea